2016
DOI: 10.1002/cphc.201600285
|View full text |Cite
|
Sign up to set email alerts
|

Quantum and Classical Molecular Dynamics of Ionic Liquid Electrolytes for Na/Li‐based Batteries: Molecular Origins of the Conductivity Behavior

Abstract: Compositional effects on the charge-transport properties of electrolytes for batteries based on room-temperature ionic liquids (RTILs) are well-known. However, further understanding is required about the molecular origins of these effects, in particular regarding the replacement of Li by Na. In this work, we investigate the use of RTILs in batteries, by means of both classical molecular dynamics (MD), which provides information about structure and molecular transport, and ab initio molecular dynamics (AIMD), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…We have previously demonstrated that the depletion of the conductivity upon the addition of salt is caused by the formation of aggregates or clusters composed by the metal cations and [Tf 2 N] − anions . These clusters induce significant changes in the microscopic structure of the electrolytes, hindering the mobility of ions and consequently reducing the conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that the depletion of the conductivity upon the addition of salt is caused by the formation of aggregates or clusters composed by the metal cations and [Tf 2 N] − anions . These clusters induce significant changes in the microscopic structure of the electrolytes, hindering the mobility of ions and consequently reducing the conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing requirements and power of these batteries, and disadvantages such as degradation or high flammability, make essential the search of alternative materials . Thanks to the high abundancy of Na as a raw material, Na‐ion batteries have attracted intense attention as potential candidates for the replacement of Li‐ion batteries . Unfortunately, Na‐ion batteries exhibit poor cycle stability and face a trade‐off between power density and energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular models for PYR14TFSI based on Lennard-Jones and Coulombic interactions were taken from Vicent-Luna et al [40,41] who demonstrated the ability of these models to reproduce the behavior of ILbased electrolytes is. The molecular models for PYR14TFSI based on Lennard-Jones and Coulombic interactions were taken from Vicent-Luna et al [40,41] who demonstrated the ability of these models to reproduce the behavior of ILbased electrolytes is.…”
Section: Methodsmentioning
confidence: 99%
“…The same attributes that make organic‐based solvents suitable electrolytes, such as high ionic conductivity, low viscosity, and high charge transfer numbers, are also ones that ILs lack at room temperature. As demonstrated in a MD‐based paper by Anta and co‐workers a lot of these less favorable transport properties are due to increased ionic correlation, which leads to larger clusters, and as a result, more sluggish diffusion in the bulk . This is especially true if the IL is composed of ions with long alkyl chains, as they promote micelle formation, which negatively affects the transport …”
Section: Electrolytes For Nibsmentioning
confidence: 99%